Equation 1: 3x + y - 2z = -7

Equation 2: -az = x + y + 6 rearranged to -x-y+3z=6 ? or x + y - 3z = -6 ? Either way, I get the same results.

1) A new set of three equations is formed using the original Equation 1 and Equation 2 and the third equation is formed by multiplying all the coefficients and the constant in Equation 1 by 3,

so the third equation is: 9x + 3y - 6z = -21

3x + y - 2z = -7

-x - y + 3z = 6

9x + 3y - 6z = -21

3x + y - 2z = -7, -x - y + 3z = 6 , 9x + 3y - 6z = -21 - Wolfram|Alpha ?

2) A new set of three equations is formed using the original Equation 1 and Equation 2 and the third equation is formed by using Equation 1 with the constant changed from -7 to 12.

3x + y - 2z = -7

-x - y + 3z = 6

3x + y - 2z = 12

I get no solution?